2013
DOI: 10.1159/000353158
|View full text |Cite
|
Sign up to set email alerts
|

Trials of Antidiabetic Drugs in Amyotrophic Lateral Sclerosis: Proceed with Caution?

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder with limited therapeutic options. Clinical trials of several drugs shown to be effective in the superoxide dismutase (SOD1) model of ALS have shown no or negative effects when tested in humans. Here we discuss the role of pioglitazone, a peroxisome proliferator-activated receptor-γ agonist, which failed to show efficacy in a recently published phase II clinical trial of ALS patients. The antioxidant and anti-inflammatory properties of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…After considering the methodologic differences, it appears that the Paganoni et al . study may actually be in agreement with studies supporting a “protective” effect of DM2 on ALS . Future studies on this important topic should employ stringent statistical analyses, include all ALS patients, and compare their findings to the full body of existing literature on the subject while reaching a conclusion regarding the prognostic value of DM2 in ALS.…”
Section: Methodological Differences Between Studies Examining Prognossupporting
confidence: 77%
“…After considering the methodologic differences, it appears that the Paganoni et al . study may actually be in agreement with studies supporting a “protective” effect of DM2 on ALS . Future studies on this important topic should employ stringent statistical analyses, include all ALS patients, and compare their findings to the full body of existing literature on the subject while reaching a conclusion regarding the prognostic value of DM2 in ALS.…”
Section: Methodological Differences Between Studies Examining Prognossupporting
confidence: 77%
“…9 A recent phase II clinical trial in MND with pioglitazone, an antidiabetic medication, resulted in an increase in mortality. 30 The mechanisms underlying changes in lipid levels and insulin resistance and how these may be protective in MND are not understood. 6 One hypothesis is that patients with MND increase their energy intake in order to compensate for a state of hypermetabolism, 5,31-34 which then results in increased lipid levels and a state of insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-diabetic drug pioglitazone improved motor performance, delayed weight loss, attenuated motor neuron loss, and extended survival in a SOD 1 mouse model [158]; however, pioglitazone failed to show efficacy in a phase II clinical trial of ALS patients [159]. Furthermore, it has been suggested that anti-diabetic drugs are detrimental in ALS in light of emerging evidence that some features of the metabolic syndrome may be protective in ALS [160]. Since pioglitazone, no further diabetic agents have been studied in ALS, and therefore the uncertainty of benefit from anti-diabetic drugs remains.…”
Section: Can These Disorders Be Corrected?mentioning
confidence: 99%